Machine vs. human, who makes a better judgment on innovation? Take GPT-4 for example - Du, Mark (Frontiers in Artificial Intelligence, 2023)
This essay explores the topic of human decision-making and the concept of noise, which refers to random and irrelevant factors that can affect decision-making. The essay argues that while humans are prone to noise in their decision-making processes, artificial intelligence (AI) can make less noise due to its ability to process large amounts of data and apply logical algorithms to make decisions. The essay examines examples and studies to demonstrate the impact of noise on human decision-making, including business ideas. Additionally, the essay highlights the potential that machine intuition is doing better than humans.